Usability assessment of web digital library: a survey among undergraduate students / Mohamad Noorman Masrek and Asad Khan. - Masrek, Mohamad Noorman; Khan, Asad (Universiti Teknologi MARA Cawangan Selangor, 2015)
Recognizing the significance of the usage construct as one of the aspect of usability assessment of the digital library (DL), this study further extends past studies by integrating this construct into commonly used criteria, namely, satisfaction, learnability, effectiveness, and efficiency. Building upon these constructs, an interrelationship model was developed and tested empirically using a survey research methodology. The learnability, effectiveness, and efficiency construct were hypothesized as significant predictors of usage and satisfaction. In addition, the usage construct was also hypothesized as a significant predictor of satisfaction. Data were collected from 320 undergraduate students from the Faculty of Information Management (FIM), Universiti Teknologi MARA (UiTM) Puncak Perdana. The results of the Structural Equation Modeling (SEM) analysis showed all postulated hypotheses were fully supported. The contribution of the study can be assessed from the theoretical and practical perspectives. The established model can be further validated in other DL implementation while the validated instrument can be used by practitioner to gauge the usability of the DL.